ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF THE ETHANOLIC EXTRACT OF THE AIR PARTS OF Solanum radicans L.F. “huallpachaqui” - García, Jorge A. (2020)
The objective of this study was to determine the antioxidant and antimicrobial activity of the ethanolic extract of the aerial parts of the Solanum radicans L.f. (huallpachaqui) from San Juan of Chacña, province of Aymaraes, department of Apurímac. The extract was taken to dryness, fractionated and determined the presence of secondary metabolites by precipitation and / or color reactions; The characterization of the extract was then carried out by determining the pH, total solids, soluble solids, ashes, color and appearance. The antioxidant activity was evaluated by the inhibition method against the radical 2,2-diphenyl-1-picrilhydrazil (DPPH) and by the Ferric Reduction Antioxidant Power (FRAP) method; the antimicrobial activity was tested in bacterial strains of Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Proteus mirabilis. The presence of secondary metabolites was identified as flavonoids, free phenolic groups, alkaloids, catechins, triterpenes and / or steroids. The antioxidant activity by the DPPH method, an IC50 of 2,77 mg /mL of extract was obtained and by the FRAP method a TEAC (1mM of trolox) was obtained for 6,59 mg /mL of extract. In the antimicrobial study, the ethanolic extract of Solanum radicans leaves showed activity against Staphylococcus aureus and Pseudomonas aeruginosa, concluding that there is a strong correlation between the presence of the secondary metabolites found and their antioxidant, and antimicrobial activity.